2008
DOI: 10.1889/jsid16.10.1063
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the dependence of optical response time of liquid‐crystal displays on the viewing direction

Abstract: Abstract— The optical response time of liquid‐crystal displays (LCDs) has recently been observed to be dependent on the viewing direction. For the vertically aligned LC mode, response time increased as the viewing angle increased when the final state is the zero gray level of the minimum luminance. This change in response time is analyzed to relate to the deformation of the normalized luminance curve of LCDs for different viewing directions. The dependency trends of the optical response time for the oblique di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…It had been reported that the temporal luminance of an LCD is affected by the viewing direction, depending on the characteristics of LC mode. [11][12][13] A simple configuration for the LC molecules of an LCD with respect to the viewing direction is illustrated in Fig. 11.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It had been reported that the temporal luminance of an LCD is affected by the viewing direction, depending on the characteristics of LC mode. [11][12][13] A simple configuration for the LC molecules of an LCD with respect to the viewing direction is illustrated in Fig. 11.…”
Section: Results and Analysismentioning
confidence: 99%
“…It had been reported that the angular dependence of the temporal behavior is not negligible for some LC modes such as TN (twisted nematic) and VA (vertical alignment). [11][12][13] Therefore, it needs to be considered how the angular dependence of the temporal behavior of LCDs affects the angular performance of SG 3D.…”
Section: Introductionmentioning
confidence: 99%
“…MPRT is affected by the temporal luminance characteristic of LCDs and the luminance depends on the viewing-angle characteristics of LCDs. 7,8 Because each LC mode has its own distinct viewing-angle characteristics, dependence of MPRT had to be considered accordingly. Users view LCDs from various directions and angles, and the vertical and horizontal directions change accordingly, depending on the viewing angles.…”
Section: Mprt Performance For the Oblique Viewing Directionsmentioning
confidence: 99%
“…7 In addition, the RT dependence on the viewing angle has been recently analyzed in detail for LCD TV. 8 In this respect, there is the possibility that the dynamic performance of LCDs is affected by the viewing angle. The current MPRT measurement system, however, is designed only for the perpendicular viewing direction and its effectiveness for measurement along the oblique viewing directions had to be considered.…”
Section: Introductionmentioning
confidence: 99%